5
$\begingroup$

During my study of generating functions, I was able to calculate the generating function of the sequence of harmonic numbers $H_n$: $$\sum_{n=1}^\infty H_nx^n=\frac{\ln(1-x)}{x-1}$$ However, I also tried to find generating functions for $H_n^2$ and $H_n^3$, with which I was unsuccessful (the rearrangement method I used for the generating function of $H_n$ didn't reduce as nicely for $H_n^2$ and $H_n^3$).

Any hints about how to find $$\sum_{n=1}^\infty H_n^2x^n=\space ?$$ and $$\sum_{n=1}^\infty H_n^3x^n=\space ?$$ Please don't write a full answer and spoil it for me - I just want a hint.

$\endgroup$
  • 2
    $\begingroup$ The form for the cubes generating function doesn't look particularly nice. See here from another post. $\endgroup$ – Foobaz John Nov 22 '17 at 0:48
  • $\begingroup$ @FoobazJohn Ooh, yuck. $\endgroup$ – Franklin Pezzuti Dyer Nov 22 '17 at 0:50
  • 1
    $\begingroup$ $f(z) = \frac{\log(1-z)}{z-1}$, then $\sum_n H_n^2 z^n = \frac{1}{2i\pi}\int_{|s| = 1/2} f(s) f(z/s) \frac{ds}{s}$ which should reduce to something with $\text{Li}_2(z)$ by partial fraction and integration by parts $\endgroup$ – reuns Nov 22 '17 at 1:22
  • $\begingroup$ @Nilknarf Hint: try to exploit the results of my recent general solution to math.stackexchange.com/questions/1073628/… $\endgroup$ – Dr. Wolfgang Hintze Nov 22 '17 at 11:50
  • $\begingroup$ First GF is possibly $\sum_{n=1}^\infty H_n^2x^n=\frac{1}{1-x}Li_2(x)$ $\endgroup$ – James Arathoon Nov 22 '17 at 12:27
3
$\begingroup$

We have that $$ f(x)=\sum_{n\geq 0}a_n x^n\quad\Longleftrightarrow\quad \frac{f(x)}{1-x}=\sum_{n\geq 0}A_n x^n $$ where $A_n = a_0+a_1+\ldots+a_n$. In order to find the OGF of $H_{n}^2$ it is enough to find the OGF of $$ H_{n+1}^2-H_{n}^2 = \left(H_{n+1}-H_n\right)\left(H_{n+1}+H_n\right)=\frac{2H_n}{n+1}+\frac{1}{(n+1)^2}, $$ and while the OGF of $\frac{1}{(n+1)^2}$ is clearly related with $\text{Li}_2(x)=\sum_{n\geq 1}\frac{x^n}{n^2}$, the OGF of $\frac{H_n}{n+1}$ can be deduced by applying termwise integration to the OGF of $H_n$. It follows that $$ \sum_{n\geq 1}H_n^2 x^n = \frac{\log^2(1-x)+\text{Li}_2(x)}{1-x}\tag{A}$$ and the (more involved) OGF of $H_n^3$ can be computed through the same trick. It is useful to consider that the Taylor series of $\log(1-x)^k$ is related to Stirling numbers of the first kind.

$\endgroup$
  • $\begingroup$ Ah-ha, so that's the trick. Well done, and thanks again! $\endgroup$ – Franklin Pezzuti Dyer Nov 23 '17 at 0:11
1
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$

Hereafter, $\ds{\bracks{\cdots}}$ is an Iverson Bracket. Namely, $\ds{\bracks{P} = 1}$ whenever $\ds{P\ \mbox{is}\ \color{red}{\texttt{true}}}$ and $\ds{0\ \color{red}{\mbox{otherwise}}}$.

\begin{align} \left.\sum_{n = 1}^{\infty}H_{n}^{2}x^{n}\,\right\vert_{\ \verts{x}\ <\ 1} & = \sum_{n = 1}^{\infty}\overbrace{\braces{\sum_{i = 1}^{\infty}{\bracks{i \leq n} \over i}}}^{\ds{H_{n}}}\ \overbrace{\braces{\sum_{j = 1}^{\infty}{\bracks{j \leq n} \over j}}}^{\ds{H_{n}}}\ x^{n} \\[5mm] & = \sum_{i = 1}^{\infty}{1 \over i}\sum_{j = 1}^{\infty}{1 \over j} \sum_{n = 1}^{\infty}\bracks{n \geq i}\bracks{n \geq j}x^{n} \\[5mm] & = \sum_{i = 1}^{\infty}{1 \over i}\sum_{j = 1}^{\infty}{1 \over j}\braces{% \bracks{i \leq j}\sum_{n = j}^{\infty}x^{n} + \bracks{i > j}\sum_{n = i}^{\infty}x^{n}} \\[5mm] & = \sum_{i = 1}^{\infty}{1 \over i}\sum_{j = 1}^{\infty}{1 \over j}\braces{% \bracks{j \geq i}\,{x^{j} \over 1 - x} + \bracks{j < i}\,{x^{i} \over 1 - x}} \\[5mm] & = {1 \over 1 - x}\sum_{i = 1}^{\infty}{1 \over i}\pars{% \sum_{j = i}^{\infty}{x^{j} \over j} + \sum_{j = 1}^{i - 1}{x^{i} \over j}} = {1 \over 1 - x}\pars{\sum_{i = 1}^{\infty}{1 \over i} \sum_{j = i}^{\infty}{x^{j} \over j} + \sum_{i = 1}^{\infty}{x^{i} \over i}\overbrace{\sum_{j = 1}^{i - 1}{1 \over j}} ^{\ds{H_{i - 1}}}} \\[5mm] & = {1 \over 1 - x}\pars{\sum_{j = 1}^{\infty}{x^{j} \over j}\ \overbrace{\sum_{i = 1}^{j}{1 \over i}}^{\ds{H_{j}}}\ + \sum_{i = 1}^{\infty}{x^{i + 1} \over i + 1}\,H_{i}} = {1 \over 1 - x}\sum_{i = 1}^{\infty} \pars{{x^{i} \over i} + {x^{i + 1} \over i + 1}}H_{i} \\[5mm] & = {1 \over 1 - x}\sum_{i = 1}^{\infty}H_{i} \pars{x^{i}\int_{0}^{1}t^{i - 1}\,\dd t + x^{i + 1}\int_{0}^{1}t^{i}\,\dd t} \\[5mm] & = {1 \over 1 - x} \pars{\int_{0}^{1}{1 \over t}\sum_{i = 1}^{\infty}H_{i}\pars{xt}^{i}\,\dd t + x\int_{0}^{1}\sum_{i = 1}^{\infty}H_{i}\pars{xt}^{i}\,\dd t} \\[5mm] & = {1 \over 1 - x}\int_{0}^{1}{1 + xt \over t} \bracks{-\,{\ln\pars{1 - xt} \over 1 - xt}}\,\dd t = -\,{1 \over 1 - x}\int_{0}^{x}{1 + t \over t\pars{1 - t}}\, \ln\pars{1 - t}\,\dd t \end{align}

because $\ds{\sum_{i = 1}^{\infty}H_{i}z^{i} = -\,{\ln\pars{1 - z} \over 1 - z}:\ \pars{~H_{i}\ Generating\ Function~}}$.

Then, \begin{align} \left.\sum_{n = 1}^{\infty}H_{n}^{2}x^{n}\,\right\vert_{\ \verts{x}\ <\ 1} & = -\,{1 \over 1 - x}\bracks{% 2\ \underbrace{\int_{0}^{x}{\ln\pars{1 - t} \over 1 - t}\,\dd t} _{\ds{-\,{1 \over 2}\,\ln^{2}\pars{1 - x}}}\ +\ \underbrace{\int_{0}^{x}\overbrace{{\ln\pars{1 - t} \over t}} ^{\ds{-\,\mrm{Li}_{2}'\pars{x}}}\ \,\dd t} _{\ds{-\,\mrm{Li}_{2}\pars{x}}}} \\[5mm] & = \bbx{\ln^{2}\pars{1 - x} + \mrm{Li}_{2}\pars{x} \over 1 - x} \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.